1973
DOI: 10.2307/1142662
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Homicide, U.S.S.R./U.S.A.: Reflections on Soviet Data in a Comparative Framework

Abstract: The general paucity of data on Soviet social conditions (in comparison to the data available from many other developed countries, including some of those in Eastern Europe) renders the exploration of sociological issues relating to the USSR rather difficult. This problem of information is especially evident when one's attention is drawn to phenomena such as crime and delinquency. Despite the growing volume of Soviet writing on these problems, "hard" data are mainly notable for their absence, and the statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Across cultures and over time homicide offenders tend to be overwhelmingly male, with most studies showing that men perpetrate 82 to 95 percent of all homicides (Carcach & Conroy, 2001; Chimbos, 1993; Connor, 1973; Kellermann & Mercy, 1992; Mouzos, 1999; Pridemore & Eckhardt, 2008; Salfati & Dupont, 2006; Shaw et al, 2006; Silverman & Kennedy, 1987; Wilbanks, 1983a; Wolfgang, 1958). Men are also the most frequent targets of lethal violence, though the sex ratio for homicide victims tends to vary more than for offenders.…”
Section: Previous Findingsmentioning
confidence: 99%
“…Across cultures and over time homicide offenders tend to be overwhelmingly male, with most studies showing that men perpetrate 82 to 95 percent of all homicides (Carcach & Conroy, 2001; Chimbos, 1993; Connor, 1973; Kellermann & Mercy, 1992; Mouzos, 1999; Pridemore & Eckhardt, 2008; Salfati & Dupont, 2006; Shaw et al, 2006; Silverman & Kennedy, 1987; Wilbanks, 1983a; Wolfgang, 1958). Men are also the most frequent targets of lethal violence, though the sex ratio for homicide victims tends to vary more than for offenders.…”
Section: Previous Findingsmentioning
confidence: 99%
“…Provocation from the victim, who is also often intoxicated as well [9,[166][167][168], often elicits impulsive violent behavior. If the resistance to provocation can be shown to be weakened by alcohol consumption, the disinhibition hypothesis is supported.…”
Section: Alcohol and Criminal Violencementioning
confidence: 99%
“…He suggested that alcohol at BAL above 0.2% disinhibits aggressive behavior. Connor [166] reported that between 70 and 80% of homicides in the Soviet Union were performed when the criminal was intoxicated. He suggested that the frustrating environment produced aggressive impulses, which became disinhibited when intoxicated.…”
Section: Alcohol and Criminal Violencementioning
confidence: 99%
“…In England and Wales, Gibson andKlein (1969, as cited in Horan, 1985) reported that quarrels and revenge responses from sexual jealousy and infidelity were the two main motives for homicide. Arguments were the main motives in the USSR (Connor, 1973 as cited in Horan, 1985) and in Israel among the Jewish population. Among the Arab population, the percentages of feud and vendetta homicides were the highest (Landau and Drapkin, 1968 as cited in Horan, 1985).…”
Section: Discussionmentioning
confidence: 98%